2009
DOI: 10.4065/84.3.221
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study of Intima-Media Thickness, Ethnicity, Metabolic Syndrome, and Cardiovascular Risk in 2268 Study Participants

Abstract: The addition of IMT to the traditional criteria for the diagnosis of the MetS may help identify individuals who otherwise would not have been identified to be at high risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Insulin resistance, hyperglycemia, and diabetes are predictors of cardiovascular events, as is the presence of the metabolic syndrome (13-16, 24, 25). Men with metabolic syndrome experience an approximate doubling of cardiovascular disease risk (25), and metabolic syndrome is also associated with preclinical atherosclerosis measured by carotid intima-media thickness in men and women (35). Our findings identify reduced serum TOC as a risk predictor for metabolic syndrome in older men, raising the possibility that circulating osteocalcin might modulate cardiovascular risk.…”
Section: Discussionmentioning
confidence: 62%
“…Insulin resistance, hyperglycemia, and diabetes are predictors of cardiovascular events, as is the presence of the metabolic syndrome (13-16, 24, 25). Men with metabolic syndrome experience an approximate doubling of cardiovascular disease risk (25), and metabolic syndrome is also associated with preclinical atherosclerosis measured by carotid intima-media thickness in men and women (35). Our findings identify reduced serum TOC as a risk predictor for metabolic syndrome in older men, raising the possibility that circulating osteocalcin might modulate cardiovascular risk.…”
Section: Discussionmentioning
confidence: 62%
“…Similar to adults [5,104], two studies performed with children and adolescents found that cIMT was increased in obese patients with metabolic syndrome compared with those without [48,75]. Furthermore, the positive relation between the number of components of metabolic syndrome and cIMT [75] in children illustrated the early synergistic effects of cardiovascular risk factors clustering on the arterial wall that was also observed in adults [2,101,104]. A parallel may be drawn with the Bogalusa Heart Study [13], an autopsy study that found a positive relation between the number of vascular risk factors and the intimal surface of coronary arteries involving fatty streaks and fibrous plaques in people from 2 to 39 years of age.…”
Section: Discussionmentioning
confidence: 78%
“…In particular, noninvasive imaging of carotid intima-media thickness (CIMT) and coronary artery calcium (CAC) scoring seem to have promising prognostic value in identifying patients at high risk [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%